Mechanical properties of reinforced concrete beam with recycled coarse aggregates / P. J. Jaua Junior, C. Petrus and J.D. Nyuin - Paul. J, Jaua Junior; Petrus, Clotilda; Nyuin, Joe Davylyn (Universiti Teknologi MARA, Perak, 2017)
The significant increment of waste concrete in recent yearsthat is happening worldwide has a tremendous consequence to the environment. Recycling concrete wastes will reduce the amount of waste as well as save natural resources, thus help promote green and sustainable development. Thisstudy presents an experimental investigation dealing with the development of green concrete using recycled concrete waste (RCWA) as coarse aggregate replacement materials. The mechanical properties of reinforced concrete (RC) beams in terms of its compressive and flexural strengths were determined. The main parameter considered is the percentage of RCWA in the concrete design of RC beams that ranges from 0% to 50%. From the test results, it was observed that the flexural strength and the compression strength decreased as the percentage of recycled concrete waste aggregate used increased. Generally, the flexural strength of RC beam with RCWA can be 5% to 12.4% lower than that of conventional concrete made with natural course aggregate.